Modifikasi Pemanasan Dengan Motivasi Belajar Siswa Dalam Pembelajaran Pendidikan Jasmani - Yusup, Muhammad Fajri; Syafei, Muhammad Mury; -, Fahrudin (Prgram Studi Pendidikan Jasmani Kesehatan dan Rekreasi, FKIP Universitas Pattimura, 2021)
This study aims to determine the relationship between heating modification and studentmotivation in learning physical education in class XI SMA Negeri 1 Jatibarang. This researchbelongs to the category of quantitative research with a correlational method. The population ofthis study were all students of class XI SMAN 1 Jatibarang, amounting to 117 people and totaledfive classes, each class numbering 23-24 people. The sampling technique used is probabilitysampling by means of simple random sampling, therefore the researcher takes a sample of 50% ofthe population or a number of 59 students to represent the entire population. Data were collectedby distributing questionnaires. The statistical analysis used was the correlation test, determinanttest, and t test. The correlation test results of 0.739 are included in the strong relationship level.Based on the results of the determinant test, it was obtained a determinant coefficient of 54.61%,which means that heating modification is an important factor in relation to learning motivation andthe remaining 45.39% is related to other factors. While the t test results obtained tcount 8,139 greater than ttable 2,002. In this case tcount is in the rejection area H0, so H0 is rejectedand H1 is accepted, meaning that there is a significant relationship between heating modificationand student learning motivation in learning physical education